Study Water Harvesting Device's Efficieny To Variation Of Environmental Factors - Nur Atifah Binti Ghazali (2023)
It is hard to obtain water resources for irrigation or other purposes in many nations such as India and Bangladesh, particularly in the arid areas. Due to absence of rainfall, the issue of water scarcity problem is also perceived in other regions of the world. Nevertheless, water can be achieved by condensing the water vapor existing in air in highly humid regions such as locations near the ocean. So, this project was designed to collect amount of water in the air using method of water condensation system based on Peltier thermoelectric cooler (TEC). It is can be considered as a solution for water scarcity problem. The system consists of a number of thermoelectric coolers, a fan to supply the required circulation of air flow, two channels of cold and hot air, heat sinks and DC power supply to power thermoelectric coolers and ventilators. It is such a device that uses the latent heat principle to convert water vapor molecules into water droplets and also it is a good implementation that stands on such a technological era that we all run behind renewable sources. The proposed of this development is to achieve maximum efficiency defined as the quantity of water produced to variation if environmental factors. Then the effects of various parameters of design are analyzed and discussed by collecting the data using sensors, microcontroller and motor driver that control the temperature of Peltier. So, this thesis describes the effectiveness of the device by experimental results and data analysis.